ANALYSIS OF FINANCIAL FACTORS AND NON-FINANCIAL FACTORS AFFECTING AUDITOR SWITCHING - Sofia, Khalida; Nur Apandi, R Nelly; Widarsono, Agus (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2024)
This study aims to determine the effect of monetary and non-monetary components on voluntary auditor turnover. Management, board, and audit committee quality are examples of non-financial impacts. Factors such as business growth, financial problems, profitability, and liquidity are included in the assessment of financial elements. Auditors can be replaced by law or voluntarily. Quantitative methods are used in this research. Specifically, this study will investigate manufacturing companies in the food and beverage industry during the period 2018-2022. Random selection of 14 companies is used as a sample method. The data analysis method used is logistic regression analysis. The results showed that the factors of management quality, board of commissioners, and audit committee did not have a significant impact on the auditor's decision to voluntarily resign. Financial crisis, profitability, and liquidity have no positive impact on voluntary auditor turnover. However, company growth has an influence on voluntary auditor turnover.